Basic German - Sedley, Beverly (Singapore : Longman, 1993)
Basic German is a course of Grammer and communicative skills. Basic Language structures for begiiners are introduced in stages, plus listenin, reading and writing task to develop essential skills.
Includes cassettes.
7-9.
Keywords: German Language -- Conversation and phrases